Bits from Blinkbonny; or, Bell o' the Manse - Strathesk, John (Salt Lake City, UT : Project Gutenberg, 2023)
"Bits from Blinkbonny; or, Bell o' the Manse" by John Strathesk is a novel written in the late 19th century. This tale encapsulates the life and dynamics within a fictional Scottish village during the years leading up to the Disruption of 1843, focusing on religious and social themes. Central to the narrative are Bell, the devoted servant of the manse, and Mr. Barrie, the parish minister, whose experiences narrate the complexities of faith, community, and personal relationships in a rural setting. The opening of the story introduces us to the manse and its inhabitants, particularly Bell and Mr. Barrie, as they navigate the challenges and joys of life in Blinkbonny. We learn about the vibrant, everyday life within the manse, including Bell's dedication to both her work and the Barrie family, and the close-knit community surrounding them. The narrative unfolds with glimpses of daily chores, heartfelt interactions, and, notably, the impact of impending changes in the Church, hinting at the larger societal conflicts that will unfold as the story progresses. The character dynamics and rich descriptions establish a strong sense of place and provide a window into the lives of the villagers during a pivotal moment in Scottish history. (This is an automatically generated summary.)
Release date is 2023-11-27
Susan Skinner, Quentin Campbell, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Villages -- Fiction; Scotland -- Social life and customs -- 19th century -- Fiction